Correlations between core muscle strength endurance and upper-extremity performance in adolescent male sub-elite handball players - Bauer, Julian; Gruber, Markus; Muehlbauer, Thomas (Frontiers in Sports and Active Living, 2022)
The objective of the study was to investigate the relationships between core muscle strength endurance (Bourban test: ventral, dorsal and lateral chain) and shoulder mobility/stability (Upper Quarter Y Balance test [YBT-UQ]) as well as throwing velocity in adolescent male sub-elite handball players (N=32, age: 17.1±0.7years). Pearson correlations were calculated for core muscle strength endurance with a) shoulder mobility/stability and b) throwing velocity. The throwing arm reach displayed significant correlations (both p<.05) between the Bourban test (ventral chain) and the inferolateral reach direction (IL) of the YBT-UQ (r=0.41) as well as the composite score (CS) (r=0.34). For the dorsal chain, significant correlations (all p<.01) were found for the medial (MD) (r=0.42) and IL (r=0.61) reach direction as well as the CS (r=0.51). For the right but not the left side of the lateral chain, significant correlations (both p<.05) were detected for the IL reach direction (r=0.40) and the CS (r=0.35). For the non-throwing arm reach, significant correlations were found between the ventral chain and the MD reach direction (r=0.53, p<.01) as well as the CS (r=0.31, p<.05). For the dorsal chain, significant correlations (all p<.01) were found for the MD (r=0.47) and IL (r=0.44) reach direction as well as the CS (r=0.41). For the lateral chain, significant correlations were detected for the MD (left and right side: r=0.49, p<.01) and IL (left and right side: r=0.35, p<.05) reach direction as well as the CS (left and right side: r=0.37, p<.05). The dorsal chain but not the ventral and lateral chain of the Bourban test showed a significant correlation with throwing velocity (r=0.33, p<.05). Our results indicate that better core muscle strength endurance is associated with better shoulder mobility/stability as well as partially higher throwing velocity of adolescent male sub-elite handball players. Therefore, practitioners should integrate core muscle strength endurance exercises into the training routines to improve upper-extremity performance of this target group.